(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The development of digital anatomical models has become a fundamental component of modern virtual surgical simulation, transforming both medical education and clinical practice. As surgical procedures become increasingly complex, the need for accurate, interactive, and patient-specific anatomical representations continues to grow. Digital models derived from high-resolution CT, MRI, and multimodal imaging enable a level of visualization and manipulation that traditional cadaveric training cannot fully provide. Using advanced techniques such as deep learning–based segmentation, 3D mesh reconstruction, biomechanical modeling, and real-time rendering, developers can create highly realistic anatomical structures that replicate tissue behavior, spatial relationships, and surgical instrument interactions. These models are integrated into virtual reality (VR), augmented reality (AR), and mixed reality platforms, offering immersive environments where surgeons can practice procedures repeatedly without risk to patients. Virtual simulations support skill acquisition, enhance decision-making, and improve operative precision—especially in complex or rare surgical scenarios. Furthermore, digital anatomical modeling plays a crucial role in personalized surgery, allowing clinicians to plan and rehearse operations using patient-specific digital twins. Despite significant progress, challenges persist, including high computational requirements, standardization of validation protocols, and the need for more accurate biomechanical algorithms. Nevertheless, ongoing advancements in artificial intelligence, cloud computing, and haptic technologies point toward a future in which digital anatomy becomes fully integrated into routine surgical education, simulation-based assessment, and clinical workflows. This article provides a comprehensive overview of the methods, technologies, applications, and future directions in the development of digital anatomical models for virtual surgical simulation.